2006
DOI: 10.1111/j.1551-2916.2006.01240.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Properties of Lead Zirconate Titanate Thin Films With a ZrO2 Buffer Layer on an Electroless Ni‐Coated Cu Foil

Abstract: The effect of zirconia (ZrO2) buffer layers on the phase development and electrical properties of lead zirconate titanate (PZT, 52/48) capacitors on an electroless Ni (P)‐coated Cu foil was investigated. It was demonstrated that the buffer layer can be used to engineer the final properties. The incorporation of the ZrO2 buffer layers retained acceptable capacitance densities (>350 nF/cm2 for 50 nm thick ZrO2), while significantly reducing leakage currents and improving reliability (<10−7 A/cm2 after 1 h at 25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Despite the fact that direct evidence of a discrete interfacial layer is not always observed by X‐ray diffraction (XRD) or microscopy techniques, the necessity of minimizing interfacial reaction layers—whether through interdiffusion of metal ions, oxidation of the substrate, extensive reduction of the dielectric, or any combination—to deposit films with high measured dielectric constants was realized by many investigators. Approaches studied include the use of oxidation‐resistant metal interlayers, 25 chemically robust interfacial oxides, 26 and conducting oxides 27,28 . In developing a technology specifically aimed at embedded capacitor applications, the work of Maria et al 25 aimed to minimize deleterious interfacial reactions by using metals with a low affinity for oxidation in concert with (Pb,La)(Zr,Ti)O 3 (PLZT) films that require low crystallization temperatures.…”
Section: Film‐on‐foilmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the fact that direct evidence of a discrete interfacial layer is not always observed by X‐ray diffraction (XRD) or microscopy techniques, the necessity of minimizing interfacial reaction layers—whether through interdiffusion of metal ions, oxidation of the substrate, extensive reduction of the dielectric, or any combination—to deposit films with high measured dielectric constants was realized by many investigators. Approaches studied include the use of oxidation‐resistant metal interlayers, 25 chemically robust interfacial oxides, 26 and conducting oxides 27,28 . In developing a technology specifically aimed at embedded capacitor applications, the work of Maria et al 25 aimed to minimize deleterious interfacial reactions by using metals with a low affinity for oxidation in concert with (Pb,La)(Zr,Ti)O 3 (PLZT) films that require low crystallization temperatures.…”
Section: Film‐on‐foilmentioning
confidence: 99%
“…To minimize interfacial oxidation and subsequent reactions, several groups have investigated both conductive and nonconductive oxide buffer layers. Nonconductive barrier layers, including Al 2 O 3 on nickel substrates for BaTiO 3 films 30 and ZrO 2 on Ni(P)/Cu substrates for PZT films 26 were investigated. This approach allowed for minimization of interfacial reactions between the high‐permittivity dielectric and the substrate, but at the cost of incorporating a low‐permittivity interface layer, which diluted the overall response and again resulted in capacitance densities limited to approximately 400 nF/cm 2 .…”
Section: Film‐on‐foilmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the presence of the buffer layer, the BsT film crystallization was improved at 800°c. This property is well known: the presence of a buffer layer decreases the temperature of perovskite phase transition [22]- [24].…”
Section: A Crystalline Propertiesmentioning
confidence: 96%
“…In addition, PZT thin films need to have a proper buffer layer to prevent or minimize interface reactions between Pb and Si or SiO 2 substrates that produce deterioration in ferroelectric properties. Also, it was demonstrated that a buffered layer can be effectively utilized to engineer the final properties of the film stack [4], because allows film orientation and microstructures, to control growth rate and film nucleation. Some buffered layer recipes have been reported in the literature such as Zirconia (ZrO 2 ), TiO 2 , Lead Titanate (PbTiO 3 or PT) and LaNiO 3 [4].…”
Section: Introductionmentioning
confidence: 99%